English remote teaching in the Amazon during the covid-19 pandemic: “Inglês no campus” experience report - Pereira Diniz, Fernanda; Koei Itikawa Tanaka, Elder; Schwade de Jesus Oliveira, Katia Lais; Piovezan Ferro, Paola; Barros de Souza Hall, Silvia Cristina (Guará Journal, 2022)
This article reports the experience in the extension project “In-glês no Campus” which had as its main goal to provide a mini-course in basic English whilst in remote learning environments. Among the theoretical basis of the project are the Communicative Approach, Task-Based Language Learning, Freirean Critical Pedagogy, and Integrated Language and Content Learning. The project team members were three professors and nine volunteer undergraduates from the Federal University of Western Pará (UFOPA) English Program. Analysis of the data revealed that the students were satisfied with the minicourse of basic English. Simultaneously, the theoretical-practical experiences related to remote teaching were well-received by the volunteers, which had a reflective attitude about the teaching and learning of the English language. Therefore, the execution of the extension project pre-sented important challenges related to teaching and learning in a remote environment during the pandemic, and it also contributed to the initial education of the English teachers, especially in reference to the use of digital technologies in teaching.